Hyperglycemia at 1h-OGTT in Pregnancy: A Reliable Predictor of Metabolic Outcomes? - Succurro, Elena; Fraticelli, Federica; Franzago, Marica; Fiorentino, Teresa Vanessa; Andreozzi, Francesco; Vitacolonna, Ester; Sesti, Giorgio (Frontiers in Endocrinology, 2021)
Gestational diabetes mellitus (GDM) is associated with a high risk of developing type 2 diabetes (T2DM) and cardiovascular disease (CVD). Identifying among GDM women those who are at high risk, may help prevent T2DM and, possibly CVD. Several studies have shown that in women with GDM, hyperglycemia at 1-h during an Oral Glucose Tolerance Test (OGTT) (1h- PG) is not only associated with an increase in adverse maternal and perinatal outcomes, but is also an independent predictor of T2DM. Interestingly, also in pregnant women who did not meet the criteria for a GDM diagnosis, 1h-PG was an independent predictor of postpartum impaired insulin sensitivity and beta-cell dysfunction. Moreover, maternal 1-h and 2-h PG levels have been found to be independently associated with insulin resistance and impaired insulin secretion also during childhood. There is evidence that hyperglycemia at 1h PG during pregnancy may identify women at high risk of future CVD, due to its association with an unfavorable CV risk profile, inflammation, arterial stiffness and endothelial dysfunction. Overall, hyperglycemia at 1h during an OGTT in pregnancy may be a valuable prediction tool for identifying women at a high risk of future T2DM, who may then benefit from therapeutic strategies aimed at preventing cardiovascular outcomes.